Analisis Resepsi Khalayak Tentang Aplikasi Mypertamina (Studi Pada Masyarakat Kota Bengkulu) - Yena Resca Gitasela; Yanto Yanto; Sri Narti (Universitas Dehasen Bengkulu, 2023)
On 01 September 2022, the government began to require the use of the MyPertamina application in the process of purchasing subsidised fuel oil, the policy implemented by the government will cause a variety of public receptions regarding the MyPertamina application. This application is relatively new to use and sophisticated so that the author is interested in conducting research to find out how the public reception analysis of the MyPertamina application. This research uses descriptive qualitative research methods with data collection techniques through observation, interviews and documentation. In this study the authors chose 6 informants who had used the MyPertamina application with different backgrounds. Then the researcher will analyse the interview results using 3 audience positions in Stuart Hall's reception theory. The results of this study indicate that 4 informants are in the Negotiated Reading position, namely the audience accepts the policies applied because this is required by the government in purchasing subsidised fuel oil but provides input and suggestions according to what they want, namely if in the future the application of using this application is no longer required then they will not use it again and in the future the performance of the MyPertamina application can be improved so that consumers have no difficulty in using it. And 2 informants in the Dominant Hegemonic Reading position where the audience fully accepts the policies applied because with this application the oil can be distributed on target. The author does not find the third position, namely Oppositional counter Hegemonic Reading, which is the audience fully rejects the policies implemented because the MyPertamina application users have felt the positive impact and benefits of using this application. This means that the results show that the audiences in this study agree with the policy of using the Mypertamina application in Bengkulu City in purchasing subsidised fuel oil (BBM).